Development of mathematics learning video based on Palembang local wisdom about prism materials - Pitriani, Pitriani (Desimal: Jurnal Matematika, 2022)
The Palembang local wisdom-based mathematics learning video is a tangible manifestation of the nation's character building through education. The developed video discusses the prism materials for eighth-graders. The video was developed through development research by adopting the ADDIE design into ADD (analysis – design – development). The purpose of the study was to examine the feasibility of learning mathematics videos based on local wisdom from experts’ judgment on material, media, and language. The research instruments were a questionnaire and a suggestion sheet. Assessment of prototype 1 showed that the video is “Feasible Enough” but needs to be improved. After revisions are made, the video is called Prototype 2. The expert’s assessment of Prototype 2 showed that the video is "Feasible" and without revision. This video is an alternative learning media (on online or offline learning, even hybrid learning). However, the potential effect remains to be seen. So, this can be a space for other researchers to continue or develop into other materials.